Association of physical function with masticatory ability and masticatory habits: a cohort study - Moeno Takeshita; Mariko Naito; Rumi Nishimura; Haruka Fukutani; Minami Kondo; Yuko Kurawaki; Sachiko Yamada; Noriyasu Uchibori (BMC, 2024)
Abstract Background Few studies have evaluated masticatory ability and habits in relation to physical function. This study aimed to investigate the association of physical function with both masticatory ability and masticatory habits. Methods In this cohort study, we followed up with 146 community-dwelling older adults aged 65-84 years for 1 year. Physical function domain scores on the Kihon Checklist were used to assess physical function. Masticatory ability was examined using objective measurements and self-administered questionnaires. Data on masticatory habits were obtained using self-administered questionnaires. The Mann-Whitney U test was used to analyze the association between masticatory ability and masticatory habits as exposures; logistic regression analysis was used to analyze the effect of exposure on the outcome. Results A relationship was found between objective and subjective masticatory ability; however, no relationship was found between objective masticatory ability and masticatory habits. Furthermore, subjective masticatory ability and masticatory habits appeared to influence physical function 1 year later (odds ratio [OR]: 6.00, 95% confidence interval [CI]: 1.44-25.05; OR: 6.49, 95% CI: 2.45-17.22). Conclusion Masticatory ability and habits may be associated with a decline in physical function after 1 year in community-dwelling older adults. To maintain the physical function of these individuals, early intervention that addresses not only masticatory ability but also masticatory habits is necessary. Graphical Abstract